The economic impact of next-generation stadiums: evidence from the Juventus Stadium using synthetic control methodology - Valerio Antolini (National Accounting Review)
This paper aimed to investigate the economic impact of building a next-generation stadium (for example, Juventus Stadium or Allianz Stadium) on real gross domestic product (GDP) per capita in the city of Turin, using an econometric methodology known as the synthetic control method. The methodology compares the post-real GDP per capita trajectory of the treated provincial economy with that of a synthetic combination of similar, but untreated, provincial economies. The analysis showed that building a next-generation stadium had a short-term effect on real GDP per capita, with an increase of approximately 2% in the year of construction (2011). Additionally, the analysis showed a spring-back effect, where in the year following the stadium's construction, the real GDP per capita is slightly lower than what is projected by the synthetic control (around 0.85%). Moreover in the subsequent years, there seems to be a small positive structural effect of the treatment since the observed outcome is always higher than the synthetic outcome. Finally, the analysis also highlights an unexpected growth in real GDP per capita compared to the synthetic control, amounting for 0.5% in the year the stadium is announced (2008). Unlike prior studies, which have merely identified correlations, this research provides the first evidence of a causal relationship between the construction of a stadium and changes in the well-being of residents within the metropolitan area where the stadium is located.